Comercio justo en el desarrollo de la economía campesina de los comerciantes del mercado municipal de Guanujo, Guaranda, 2022. - González Medina, Juan Patricio (2023)
In the present investigative work, the level of knowledge that the merchants of the municipal market of Guanujo have regarding fair trade and peasant economy was analyzed, for this reason it has been seen the need to investigate the factors that prevent the practice of fair trade at the time of sell your products. In addition, in the investigation it is exposed that trade is an activity of exchanges or barters that primitive man has practiced to survive, in the course of time fair trade appears to establish and regulate prices in order to obtain fair payments for the sale of the products, thus becoming an indispensable activity for the human being. The methods that were used in the development of the investigative work are: exploratory and descriptive method because part of the general problem allowing to know the factors that influence the ignorance that merchants have about the concept of fair trade, the type of investigation was used quantitative with which a questionnaire of questions was applied that helped to know real data of the investigation. The results obtained showed that the merchants have little knowledge about the concept of fair trade, this is due to the lack of socialization on the subject by the administrators and authorities on duty. Keywords: Fair trade, peasant economy, merchants, sociology of work, rural sociology